2015
DOI: 10.1089/ten.tea.2013.0331
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted:Promoting the Recovery of Injured Liver with Poly (3-Hydroxybutyrate-Co-3-Hydroxyvalerate-Co-3-Hydroxyhexanoate) Scaffolds Loaded with Umbilical Cord-Derived Mesenchymal Stem Cells

Abstract: Cell-based therapies are major focus of current research for treatment of liver diseases. In this study, mesenchymal stem cells were isolated from human umbilical cord Wharton's jelly (WJ-MSCs). Results confirmed that WJ-MSCs isolated in this study could express the typical MSC-specific markers and be induced to differentiate into adipocytes, osteoblasts, and chondrocytes. They could also be induced to differentiate into hepatocyte-like cells. Poly (3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The matrices derived were loaded with human umbilical cord multipotent stromal cells (MSCs) and hepatocyte-like cells, and after 28 days the tissue generated looked very similar to the native organ. A study reported the recovery of injured mouse liver when a PHBVHHx scaffold loaded with human umbilical cord Wharton’s jelly (WJ) MSCs was transplanted [133]. Chemically modified PHAs also find use as films, pins, sutures, screws, and scaffolds for repairing skin, cartilage and LTE [111].…”
Section: Hydrogels For Ltementioning
confidence: 99%
“…The matrices derived were loaded with human umbilical cord multipotent stromal cells (MSCs) and hepatocyte-like cells, and after 28 days the tissue generated looked very similar to the native organ. A study reported the recovery of injured mouse liver when a PHBVHHx scaffold loaded with human umbilical cord Wharton’s jelly (WJ) MSCs was transplanted [133]. Chemically modified PHAs also find use as films, pins, sutures, screws, and scaffolds for repairing skin, cartilage and LTE [111].…”
Section: Hydrogels For Ltementioning
confidence: 99%
“…PHBVHHx is considered a promising PHA member for the growth of stem cells, and certain studies utilized it as biomaterial for the preparation of three-dimensional supportive scaffolds for organ tissue. In some works [50,51], PHBVHHx films and scaffolds were developed and loaded with mesenchymal stem cells from human umbilical cord (UC-MSCs) to recover injured liver. Biopolymer scaffolds were transplanted into liver-injured mice, and the results demonstrated that the PHA scaffold significantly promoted the recovery of injured liver and could be used for liver tissue engineering.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Biopolymer scaffolds were transplanted into liver-injured mice, and the results demonstrated that the PHA scaffold significantly promoted the recovery of injured liver and could be used for liver tissue engineering. In the case of the work by Li et al [50], differences between PHBVHHx and some other commonly used biopolymers such as PLA, PHB4HB, and PHBHHx were examined by loading them with stem cells into their scaffolds (Figure 2d). They concluded that the PHBVHHx structures exhibited the highest cell attachment and, when loaded with mesenchymal stem cells, significantly improved the recovery of injured liver.…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one drawback of the mcl-PHAs for electrospinning is their low glass transition temperature (T g ), which limits their spinnability and causes sticky and fused fibers. Several groups have investigated the electrospinning of different scl-PHAs, including P(3HB), poly(3-hydroxybutyrate- co -3-hydroxyvalerate) P(3HB- co -3HV), poly(3-hydroxybutyrate- co -4-hydroxybutyrate) (P3HB- co -4HB), poly(3-hydroxybutyrate- co -3-hydroxyhexanoate) P(HB- co -3HHx) and poly(3-hydroxybutyrate- co -3-hydroxyvalerate- co -3-hydroxyhexanoate) P(3HB- co -3HV- co -3HHx) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Recent examples by Liu and coworkers introduced both single-nozzle and coaxial electrospinning of mcl-PHA poly (3-hydroxyoctanoate- co -3-hydroxyhexanoate) P(3HO- co -3HHx) nanofibers by blending with a scl-PHA, P(3HB- co -3HV) [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%